EM− Graded Rings - Tariq Alraqad; Hicham Saber; Rashid Abu-Dawwas (Journal of Mathematics)
The main goal of this article is to introduce the concept of EM−G− graded rings. This concept is an extension of the notion of EM− rings. Let G be a group, and R be a G− graded commutative ring. The G− gradation of R can be extended to Rx by taking the components Rxσ=Rσx. We define R to be an EM−G− graded ring if every homogeneous zero divisor polynomial has an annihilating content. We provide examples of EM−G− graded rings that are not EM− rings, and we prove some interesting results regarding these rings.